(untitled) (International Congress on Economics, Management and Business Studies, 2026)
Cross-border remittances have become an important financial source for many developing economies, contributing significantly to income stability, poverty reduction, and domestic demand growth. This thesis examines international experience in the effective use of cross-border remittances for national economic development. Special attention is paid to the mechanisms through which remittance flows support household consumption, stimulate small business activity, and enhance investment potential. Based on the analysis of global practices, key policy approaches aimed at increasing the developmental impact of remittances are identified. The findings highlight the importance of improving financial infrastructure, expanding digital transfer systems, and creating favorable institutional conditions to transform remittance inflows into a sustainable driver of economic growth.